Nutritional Therapy Based on ESPEN Guidelines in a Patient with Ascending Colon Non-Hodgkin Lymphoma Undergoing Chemotherapy with Decreased Oral Intake and Infectious Complications: A Case Report - Ni Komang Saraswita Laksmi (Bali Medical and Wellness Journal, 2026)
Background: Malnutrition is a frequent complication in patients with cancer undergoing chemotherapy due to increased metabolic requirements, treatment-related adverse effects, and infectious complications. Gastrointestinal disturbances such as nausea, dysphagia, and opportunistic infections may worsen food intake and increase the risk of malnutrition. Case Description: A 66-year-old woman with ascending colon non-Hodgkin lymphoma undergoing the fourth cycle of R-CHOP chemotherapy was hospitalized with pneumonia, oroesophageal candidiasis, suspected pneumonitis, electrolyte disturbances (Na 129 mmol/L; K 3.2 mmol/L), and mild anemia (Hb 9.8 g/dL). Nutritional assessment showed a body mass index of 19.2 kg/m2 with approximately 10.6% weight loss during the chemotherapy period, indicating a risk of malnutrition. Nutritional therapy was provided gradually as a high-energy, high-protein diet with targets of 2100 kcal and 70 g protein/day, in the form of blenderized meals three times daily, together with peptide-based enteral formula supplementation, additional virgin coconut oil, and zinc and vitamin C supplementation. Discussion: Texture modification was intended to improve oral tolerance and minimize discomfort during swallowing, whereas the peptide-based formula was selected because it may be more easily absorbed when gastrointestinal function is impaired. The addition of virgin coconut oil as a source of medium-chain triglycerides provided energy that is rapidly metabolized without complex emulsification. Zinc and vitamin C supplementation was expected to support immune response, reduce oxidative stress, and accelerate the healing of mucosa inflamed due to infection and chemotherapy-related effects. Conclusion: A combination of food texture modification, peptide-based formula, and rapidly absorbed energy sources is a rational strategy to maintain nutritional adequacy and prevent worsening nutritional status during chemotherapy. Keywords: non-Hodgkin lymphoma, chemotherapy, malnutrition, ESPEN